WATER SUPPLY FOR NEWLY INCLUDED EIGHTEEN WARDS IN DHAKA NORTH CITY CORPORATION: AN INTROSPECTION - Muhammad Sanaullah (International Journal of Innovations in Engineering Research and Technology, 2021)
Dhaka, the capital of Bangladesh and a city with 20 million inhabitants, faces numerous challenges such as water logging, ground water depletion, inadequate sanitation, polluted river water, unplanned urban development, and the existence of large slums where more than one third of its population lives. Residents of Dhaka enjoy one of the lowest water tariffs in the world, which limits the utility’s capacity to invest. The utility in charge of water and sanitation in Dhaka, DWASA, addresses these challenges. By this way, operating costs are more than covered, and a reduction of water losses from 53% in 2003 to 29% in 2010. For these achievements DWASA, got a "Performer of the Year Award" at the Global Water Summit 2011 in Berlin. The award selection was made by participants based on presentations by the managers of seven invited utilities from Algeria, Bangladesh, Brazil, Poland, Romania and the United States. In the future DWASA plans massive investment to replace dwindling groundwater resources with treated surface water from less polluted rivers located up to 160 km from the city. In 2011 Bangladesh’s capital development authority, Rajdhani Unnayan Kartripakkha (RAJUK), made rainwater harvesting for new houses mandatory in an effort to address water scarcity and reduce flooding. The inclusion of Eighteen wards in DNCC aims to improve the availability, safe and quality of water in a sustainable way. There are number of studies found, where the water supply in Dhaka City areas are considered as main focus. This study found the gap of water supply in DNCC after Eighteen wards were included in the corporation.